2020
DOI: 10.3390/genes11060700
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed miRNA-Gene Targets Related to Intramuscular Fat in Musculus Longissimus Dorsi of Charolais × Holstein F2-Crossbred Bulls

Abstract: Intramuscular fat (IMF) is a meat quality indicator associated with taste and juiciness. IMF deposition, influenced by genetic and non-genetic factors, occurs through a transcriptionally coordinated process of adipogenesis. MicroRNAs (miRNAs) are transcriptional regulators of vital biological processes, including lipid metabolism and adipogenesis. However, in bovines, limited data on miRNA profiling and association with divergent intramuscular fat content, regulated exclusively by genetic parameters, have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…MiRNAs are small non-coding RNAs that are approximately 22 nucleotides long [ 28 ]. A single miRNA can regulate the expression of multiple genes through post-transcriptional repression and epigenetic regulation, making miRNAs the major regulators of gene expression [ 28 , 29 , 30 , 31 , 32 ]. Several studies have shown the role of miRNAs and their target genes in skeletal muscle growth and development at different prenatal and postnatal stages across different breeds of pigs [ 23 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are small non-coding RNAs that are approximately 22 nucleotides long [ 28 ]. A single miRNA can regulate the expression of multiple genes through post-transcriptional repression and epigenetic regulation, making miRNAs the major regulators of gene expression [ 28 , 29 , 30 , 31 , 32 ]. Several studies have shown the role of miRNAs and their target genes in skeletal muscle growth and development at different prenatal and postnatal stages across different breeds of pigs [ 23 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are highly conserved short non-coding RNAs which regulate gene expression by degradation or translational inhibition of their target mRNAs 27 . MiRNAs regulate several biological and cellular processes in a variety of tissues across different animal species 28 30 . Various networks of miRNAs were identified in intestinal epithelial cells, which indicates the potential role of miRNAs in regulating nutrient metabolism and intestinal secretions 31 .…”
Section: Introductionmentioning
confidence: 99%
“…This, together with our previous results from mRNA/miRNA profiling in bovine muscle with different IMF content motivated our current study. In our previous microarray screen, we found upregulation of miR-100 and downregulation of IGF1R in bovine LD muscles with high IMF content compared to low IMF content [49,50]. Whether this negative correlation exists in primary bovine muscle cells or if miR-100 plays a causal role in muscle cell proliferation and differentiation and lipid accumulation by targeting IGF1R remains unclear.…”
Section: Introductionmentioning
confidence: 93%